PERANAN HUKUM TERHADAP PERMASALAHAN JUDI ONLINE YANG BERDAMPAK PADA EKONOMI NASIONAL - Saputra Nasution, Muhammad Sakti; Suryani, Meria; Onasis, Rindang; Vitaria, Berlian; Aziz Hakim, Syaefa; Rai Adriani, Gusti; Parulian, Samuel; Ruslina, Elli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The development of technology and economy has influenced the emergence of a new form of crime, such as the crime of gambling in a new way. Gambling itself is an act that is self-defeating and against the law. But the development of the gambling system to the online realm has resulted in more and more interest in the community to take part in this development either as an online gambling player. Online gambling crime has several factors that cause people to be interested, namely social and economic factors, making gambling as an easy way to improve their standard of living, by using a small amount of money they have the hope of getting a large profit or becoming rich. Environmental factors are also a factor in this gambling crime.Online gambling has a bad impact, even threatening the national economy. The circulation of online gambling money is very large, but it does not create asset growth. In fact, the money used for gambling can actually be used for more productive purposes. When channeled for gambling, money leaves the productive economic cycle and enters circulation that does not provide added value to the wider community. Online gambling addiction causes severe financial pressure, pushing individuals to commit crimes to fulfill their needs or maintain their addiction. This condition causes them to act beyond reason.Keywords: Online Gambling, Role of Law, Economy, Social